A high-performance beak-shaped castable and its preparation method
By using magnesium-aluminum mixed liquid prepared by magnesium acetate and alkali aluminum acetate, the first aggregate and electromelted white corundum fired by alumina ball mill, combined with composite coated graphite powder and other powders, a high-performance hawk-bow castable with a micro-nanopore structure is formed, which solves the problem of traditional castables being susceptible to erosion in high-temperature environments, and achieves comprehensive performance of high strength, stability and erosion resistance.
Patent Information
- Application Number
- CN202411649099.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Traditional chute castables are susceptible to erosion by copper liquid and slag in high temperature environments, resulting in a short service life. The volume of mullite corundum castables changes greatly at high temperatures, affecting the shape of the finished product.
The first aggregate (a mixture of magnesium-aluminum prepared from magnesium acetate and alkaline aluminum acetate and alumina ball mill) and electromelted white corundum are used as aggregates, combined with composite coated graphite powder, silicon nitride, α-alumina micropowder, silica micropowder and barium sulfate and other powders, and calcium aluminate cement and composite dispersant are used as binding agents and dispersants to form a high-performance hawk-mouth castable with a micro-nanopore structure.
This high-performance eagle-mouth castable has a small bulk density, a large porosity, a large flexural strength and a large pressure resistance, a small permanent line change rate, a small expansion resistance, a good thermal shock resistance, and a good explosion resistance, and can effectively resist the corrosion of copper liquid slag.
Smart Images

Figure CN119143486B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of castables, and more specifically, to a high-performance hawkbill castable and a preparation method thereof. Background Art
[0002] In the industrial field, copper liquid is often used in high-temperature environments for various production, processing and treatment processes. A chute for molten metal is used in the smelting and smelting transfer of copper. Traditional chutes are generally built with clay bricks, magnesia bricks and magnesia-chrome bricks mixed with fire mud. However, due to the low viscosity of metallic copper liquid at high temperatures, the copper liquid has serious corrosion problems on traditional chute castables and has a low service life. Specifically, the copper liquid flows from the furnace through the chute to the swing tundish. The chute castable is easily damaged due to the combined effects of high-temperature scouring, penetration and chemical erosion of the copper liquid and slag, as well as rapid temperature changes and long-term high-temperature operations, which reduces the performance of the castable, thereby affecting production efficiency and product quality.
[0003] At present, the castables with excellent high temperature resistance and resistance to copper molten slag corrosion performance include mullite corundum castables and corundum-spinel refractory castables. Mullite corundum castables have many excellent properties, such as strong refractory performance, corrosion resistance, high temperature stability, and good wear resistance. However, the thermal expansion coefficient of mullite corundum castables is large, and when used at high temperatures, it may produce a large volume change, which will affect the close contact between the castable and the lined equipment, resulting in a large change in the shape of the cast product from the preset shape.
[0004] Therefore, a high-performance castable is needed, which should have high strength, good high-temperature volume stability, thermal shock resistance, permeability resistance and erosion resistance. Summary of the invention
[0005] In order to further improve the comprehensive performance of the chute castable, the present application provides a high-performance hawkbill castable and a preparation method thereof.
[0006] In the first aspect, the present application provides a high-performance hawkbill castable, which adopts the following technical solution:
[0007] A high-performance hawkbill castable comprises the following raw materials by weight: 45-65 parts of a first aggregate, 15-20 parts of fused white corundum, 10-15 parts of composite coated graphite powder, 3-5 parts of silicon nitride, 4-6 parts of alpha-alumina micropowder, 2-2.5 parts of silicon dioxide micropowder, 2-4 parts of calcium aluminate cement, 0.3-0.5 parts of a composite dispersant, 0.1-0.3 parts of barium sulfate, 5-7 parts of water, 0.5-0.8 parts of tris(2-hydroxypropionic acid)aluminum salt, and 0.8-1 parts of an activator.
[0008] By adopting the above technical scheme, the first aggregate and fused white corundum are used as aggregates, composite coated graphite powder, silicon nitride, α-alumina powder, silica powder and barium sulfate are used as powders, calcium aluminate cement is used as a binder, sodium hexametaphosphate and sodium tripolyphosphate are used as composite dispersants, and tri(2-hydroxypropionic acid)aluminum salt and an active agent are used as auxiliary agents. The prepared high-performance hawkbill castable has the characteristics of small bulk density, large apparent porosity, large flexural strength and compressive strength, small permanent linear change rate, expansion resistance, good thermal shock stability, good burst resistance, and resistance to erosion by copper liquid slag.
[0009] Preferably, the preparation method of the first aggregate comprises the following steps: 1.1, dissolving magnesium acetate and basic aluminum acetate in deionized water in proportion, stirring and mixing evenly, then dropping (8-10) wt% of dilute ammonia water at room temperature, and simultaneously dropping acetic acid to obtain a magnesium-aluminum mixed solution; 1.2, mixing alumina, the magnesium-aluminum mixed solution, and polyvinyl alcohol, then ball milling, pressing and molding, to obtain a blank; 1.3, keeping the blank at 1700-1800°C for 3-5h, and then crushing and grading to obtain the first aggregate.
[0010] By adopting the above technical scheme, magnesium acetate and basic aluminum acetate are used to prepare a magnesium-aluminum mixed liquid, and then the first aggregate having a corundum and aluminum-rich spinel phase is sintered by ball milling with alumina and polyvinyl alcohol, and its volume density is reduced by the micro-nano pore structure, the total porosity is increased, and the thermal conductivity is reduced. When in use, the copper molten slag enters the pores of the first aggregate due to the surface tension, and contacts with the aluminum-rich spinel in the pores. The first aggregate is dissolved in the copper molten slag, and the magnesium-iron and aluminum-iron composite spinel are saturated and crystallized. Calcium oxide reacts with aluminum oxide to form a tight calcium hexaaluminate plate layer, which significantly improves the anti-copper molten slag penetration function of the pore area, and effectively inhibits the further penetration and erosion of the copper molten slag.
[0011] Preferably, the magnesium acetate and basic aluminum acetate are weighed according to a magnesium-aluminum mass ratio of 12-15:50-55; the dosage ratio of magnesium acetate, deionized water, dilute ammonia water, and acetic acid is: (4.8-5.5) g: (15-20) mL: (6.5-7.2) mL: (0.8-1.2) mL; the dosage ratio of aluminum oxide, magnesium-aluminum mixed solution, and polyvinyl alcohol is (50-70) g: (10-20) mL: (2.4-3.6) g.
[0012] By adopting the above technical solution, the prepared first aggregate has uniform pores, small size and micro-nano pore structure.
[0013] Preferably, the preparation method of the composite coated graphite powder is as follows: 2.1, silicon powder and graphite are mixed, ground for 10-15 minutes, then boron powder is added, ground for 10-15 minutes, and then a uniformly mixed sodium fluoride and potassium fluoride mixed salt is added, and mixing is continued for 15-20 minutes to obtain a mixture; 2.2, the mixture is heated to 1300-1500°C under an argon atmosphere and kept warm for 2-3 hours, and cooled to room temperature; repeatedly washed with deionized water, and after sufficient drying, a composite coated graphite powder is obtained.
[0014] By adopting the above technical solution, after grinding graphite and silicon powder, adding boron powder for grinding, and finally adding composite salt for grinding and high-temperature heat treatment, a silicon carbide whisker coating layer is formed in situ on the graphite surface, and at the same time, silicon powder and boron powder form silicon boride and deposit on the silicon carbide whisker coating layer. On the one hand, silicon carbide and silicon boride enhance the wettability of graphite, and enhance its compatibility and bonding ability with other components; on the other hand, silicon carbide and silicon boride can be oxidized in the process of contact with copper liquid slag to form silicon dioxide and boron trioxide anti-oxidation layers, which prevent graphite from rapid oxidation and improve its oxidation resistance, which is conducive to giving full play to the graphite's anti-metal liquid corrosion characteristics. At the same time, the formed silicon carbide whiskers are conducive to improving its high-temperature flexural strength.
[0015] Preferably, the dosage ratio of the silicon powder, boron powder, graphite and mixed salt is (10-20) g: (5-8) g: (18-30) g: (2.4-3.6) g; the mass ratio of sodium fluoride to potassium fluoride in the mixed salt is 6-10: 5-8; the particle size of the graphite is less than 0.025 mm, and the particle sizes of the silicon powder and boron powder are less than 0.01 mm.
[0016] By adopting the above technical solution, the boride and silicon carbide whisker coating layers of the prepared composite coated graphite powder are compact, which is beneficial to further improve the anti-oxidation performance of the composite coated graphite powder.
[0017] Preferably, the composite dispersant is a mixture of sodium hexametaphosphate and sodium tripolyphosphate in a mass ratio of (8-10): (3-5); the components of the active agent include 39-43wt% aluminum oxide, 12-15wt% calcium oxide and 16-20wt% magnesium oxide, and the active agent d50 is 10-20 microns.
[0018] By adopting the above technical scheme, the use of a composite dispersant helps to reduce the viscosity of the slurry during the preparation of high-performance hawkbill castables and improve its slurry rheology; the use of a hydrotalcite-like phase formed by the addition of tri(2-hydroxypropionic acid) aluminum salt and an active agent can reduce the negative effects of its hydration expansion, enhance its permeability and strength, improve its explosion-proof performance, and reduce the permanent linear expansion rate.
[0019] Preferably, the mass percentages of various particle sizes in the first aggregate are: 1-3mm, 25-40%; 3-8mm, 20-35%; 8-15mm, 12-25%; 15-25mm, 8-15%; the mass percentages of various particle sizes in fused white corundum are: 1-3mm, 30-45%; 8-15mm, 55-70%.
[0020] By adopting the above technical solution, the first aggregate is used to replace most of the fused white corundum, which is beneficial to enhancing its ability to resist corrosion by molten copper slag.
[0021] Preferably, the particle size of the composite coated graphite powder is less than 0.04 mm, the particle size of silicon nitride is less than 0.03 mm, the particle size of α-alumina powder is less than 0.03 mm, and the particle size of silicon dioxide powder is less than 0.03 mm.
[0022] By adopting the above technical solution, the use of micropowders with a particle size below is beneficial to the casting and firing process. Alumina and silica micropowders react to form a mullite binding phase, thereby improving its thermal shock stability. Silicon nitride and silica micropowders form Si 2 N 2 O cementing phase, improving its flexural strength and compressive strength as well as its resistance to penetration by molten copper slag.
[0023] In the second aspect, the present application provides a method for preparing a high-performance hawkbill castable, comprising the following steps: 3.1, premixing composite coated graphite powder, silicon nitride, α-alumina powder, silica powder, composite dispersant, barium sulfate, tri(2-hydroxypropionic acid) aluminum salt, activator and calcium aluminate cement in proportion, then adding the first aggregate and fused white corundum to mix evenly, then adding water and stirring evenly, then pouring into shape, curing for 20-24 hours, and then demolding to obtain a casting; 3.2, curing the casting for another 168-170 hours, then heating it to 600-650°C for the first time, keeping it warm for 1-2 hours, and then heating it to 750-900°C for the second time, keeping it warm for 3-5 hours, to obtain a high-performance hawkbill castable.
[0024] Preferably, the first heating rate is 8-10°C / min, and the second heating rate is 3-5°C / min.
[0025] By adopting the above technical solution and using two-stage sintering, it is possible to reduce cracks in high-performance hawkbill castables during the firing process, prevent bursting, and promote the generation of a bonding phase between production raw materials.
[0026] In summary, this application has the following beneficial effects:
[0027] 1. The present application adopts the first aggregate and fused white corundum as aggregate, composite coated graphite powder, silicon nitride, α-alumina powder, silica powder and barium sulfate as powder, calcium aluminate cement as binder, sodium hexametaphosphate and sodium tripolyphosphate as composite dispersants, tri(2-hydroxypropionic acid)aluminum salt and activator as adjuvants. Through the interaction between the materials, the high-performance eagle beak castable obtained has the characteristics of high flexural strength and compressive strength, small permanent linear change rate, expansion resistance, good thermal shock stability, good burst resistance, and resistance to erosion by copper liquid slag.
[0028] 2. In the present application, magnesium acetate and basic aluminum acetate are preferably used to prepare a magnesium-aluminum mixed liquid, which is then ball-milled and sintered with alumina and polyvinyl alcohol to form a first aggregate having a corundum and aluminum-rich spinel phase. The volume density is reduced by the micro-nano pore structure, the total porosity is increased, and the thermal conductivity is reduced. The copper molten slag enters the pores of the first aggregate due to surface tension and contacts with the aluminum-rich spinel in the pores. The first aggregate is dissolved in the copper molten slag, and the magnesium-iron and aluminum-iron composite spinel is saturated and crystallized. Calcium oxide reacts with aluminum oxide to form a compact calcium hexaaluminate plate layer, which significantly improves the anti-copper molten slag penetration function of the pore area and effectively inhibits the further penetration and erosion of the copper molten slag.
[0029] After grinding graphite and silicon powder, adding boron powder and grinding, and finally adding composite salt and grinding, a silicon carbide whisker coating is formed in situ on the graphite surface after high-temperature heat treatment. At the same time, silicon powder and boron powder form silicon boride and deposit on the silicon carbide whisker coating. On the one hand, silicon carbide and silicon boride enhance the wettability of graphite, and enhance its compatibility and bonding ability with other components; on the other hand, silicon carbide and silicon boride can be oxidized in the process of contact with copper molten slag to form silicon dioxide and boron trioxide antioxidant layers, which prevent rapid oxidation of graphite and improve its antioxidant properties, which is conducive to giving full play to the graphite's resistance to metal liquid corrosion. At the same time, the silicon carbide whiskers formed are conducive to improving its high-temperature flexural strength.
[0030] By adding alumina and silica powder, it can react at high temperature to form mullite binding phase, improving its thermal shock stability; by adding silicon nitride and silica powder, it is beneficial to form Si at high temperature. 2 N 2 O cementing phase, improves its flexural strength and compressive strength as well as its resistance to metal penetration. The barium feldspar phase is generated by barium sulfate, aluminum oxide and silicon dioxide powder to improve its anti-corrosion effect; the hydrotalcite phase is formed by the addition of tri(2-hydroxypropionic acid) aluminum salt and an active agent, which can reduce the negative effects of its hydration expansion, enhance its permeability and strength, improve its explosion-proof performance, and reduce the permanent linear expansion rate. In addition, silicon carbide and silicon nitride are also beneficial to increase the wetting angle of its copper molten slag, making it difficult for the copper molten slag to penetrate, thereby improving its ability to resist metal penetration.
[0031] 3. The high-performance eaglebill castable prepared by the preparation method of the present application has the characteristics of high flexural strength and compressive strength, expansion resistance, good thermal shock stability, good burst resistance, and resistance to erosion by copper liquid slag. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 : SEM image of the first aggregate prepared in Example 2 of the present application (left: 50um, right: 1um).
[0033] Figure 2 : SEM image of the composite coated graphite powder prepared in Example 2 of the present application.
[0034] Figure 3 : Cross-sectional erosion SEM images of high-performance eaglebill castables, where (a) is Example 1; (b) is Example 2; (c) is Example 3; (d) is Comparative Example 1; (e) is Comparative Example 1; (f) is Comparative Example 1.
[0035] Figure 4 : Structural shape diagram of the high-performance hawkbill castable prepared in this application. DETAILED DESCRIPTION
[0036] The present application is further described in detail below with reference to the embodiments.
[0037] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available. Example 1
[0038] A high-performance hawkbill castable, comprising the following raw materials by weight: 45 parts of first aggregate, 15 parts of fused white corundum, 10 parts of composite coated graphite powder, 3 parts of silicon nitride, 4 parts of α-alumina micropowder, 2 parts of silicon dioxide micropowder, 2 parts of calcium aluminate cement, 0.3 parts of composite dispersant, 0.1 parts of barium sulfate, 5 parts of water, 0.5 parts of tris(2-hydroxypropionic acid) aluminum salt, and 0.8 parts of activator;
[0039] The composite dispersant is a mixture of sodium hexametaphosphate and sodium tripolyphosphate in a mass ratio of 8:3;
[0040] The mass percentage of each particle size in the first aggregate is: 1-3mm, 25%; 3-8mm, 35%; 8-15mm, 25%; 15-25mm, 15%;
[0041] The mass percentages of the particle sizes in the fused white corundum are: 1-3mm, 45%; 3-8mm, 55%;
[0042] The particle size of the composite coated graphite powder is less than 0.04 mm, the particle size of silicon nitride is less than 0.03 mm, the particle size of α-alumina micropowder is less than 0.03 mm, and the particle size of silicon dioxide micropowder is less than 0.03 mm.
[0043] The preparation method of the high-performance hawkbill castable comprises the following steps:
[0044] 1. Preparation of the first aggregate:
[0045] 1.1, dissolve magnesium acetate and basic aluminum acetate in deionized water in proportion, stir and mix evenly, then drop 8wt% dilute ammonia water at room temperature, and simultaneously drop acetic acid to obtain a magnesium-aluminum mixed solution; the magnesium acetate and basic aluminum acetate are weighed according to a magnesium-aluminum mass ratio of 12:50; the dosage ratio of the magnesium acetate, deionized water, dilute ammonia water, and acetic acid is: 4.8g:15mL:(6.5-7.2)mL:0.8mL;
[0046] 1.2, alumina, magnesium-aluminum mixed solution and polyvinyl alcohol are mixed, then placed in a ball mill for ball milling, and pressed under 120 MPa to obtain a blank; the amount ratio of alumina, magnesium-aluminum mixed solution and polyvinyl alcohol is 50g:10mL:2.4g;
[0047] 1.3. Place the blank in a firing kiln, heat it to 1800°C at a rate of 5°C / min, keep it warm for 3 hours, and then crush and classify it to obtain the first aggregate.
[0048] The first aggregate obtained mainly includes corundum phase and aluminum-rich spinel phase; the bulk density is 3.02g / cm 3 The total porosity is 18.7%. The pore size is uniform, mainly concentrated in the range of 8-10 microns. The inner surface of the pores is a micro-nano pore structure formed by an aluminum-rich spinel phase. The thermal conductivity is 5.1 W / (m·K) at 700°C.
[0049] 2. Preparation of composite coated graphite powder:
[0050] 2.1. Mix silicon powder and graphite, grind for 10 minutes, then add boron powder, continue grinding for 10 minutes, then add a uniformly mixed sodium fluoride and potassium fluoride mixed salt, continue mixing for 15 minutes to obtain a mixture; the amount ratio of the silicon powder, boron powder, graphite and mixed salt is 10g:5g:18g:2.4g; the mass ratio of sodium fluoride and potassium fluoride in the mixed salt is 6:5; the graphite is flaky graphite, the particle size of the graphite is less than 0.025mm, and the particle size of the silicon powder and boron powder is less than 0.01mm.
[0051] 2.2, the mixture is heated to 1300°C in an argon atmosphere and kept at this temperature for 3 hours, and then cooled to room temperature; it is repeatedly washed with deionized water, and fully dried at 100°C to obtain composite coated graphite powder.
[0052] The composite coated graphite powder is a graphite structure coated with silicon hexaboride crystals and silicon carbide whiskers.
[0053] 3. Preparation of high-performance eaglebill castables:
[0054] 3.1, premix composite coated graphite powder, silicon nitride, α-alumina powder, silica powder, composite dispersant, barium sulfate, tri(2-hydroxypropionic acid) aluminum salt, activator and calcium aluminate cement in proportion, then add the first aggregate and fused white corundum and mix evenly, then add water and stir evenly, then cast into shape, cure at room temperature for 20 hours, then demold to obtain a cast product; the active agent comprises 39wt% alumina, 15wt% calcium oxide and 20wt% magnesium oxide, and the active agent d 50 10 microns;
[0055] 3.2, the casting is cured at room temperature for 168h, then heated to 600℃ at a rate of 8℃ / min for the first time, kept warm for 2h, and then heated to 750℃ at a rate of 3℃ / min for the second time, kept warm for 5h, to obtain high-performance hawkbill casting material. Example 2
[0056] A high-performance hawkbill castable, comprising the following raw materials by weight: 55 parts of first aggregate, 18 parts of fused white corundum, 13 parts of composite coated graphite powder, 4 parts of silicon nitride, 5 parts of α-alumina powder, 2.2 parts of silicon dioxide powder, 3 parts of calcium aluminate cement, 0.4 parts of composite dispersant, 0.2 parts of barium sulfate, 6 parts of water, 0.6 parts of tris(2-hydroxypropionic acid)aluminum salt, and 0.9 parts of activator;
[0057] The composite dispersant is a mixture of sodium hexametaphosphate and sodium tripolyphosphate in a mass ratio of 9:4;
[0058] The mass percentage of each particle size in the first aggregate is: 1-3mm, 35%; 3-8mm, 30%; 8-15mm, 20%; 15-25mm, 15%;
[0059] The mass percentages of the particle sizes in the fused white corundum are: 1-3mm, 40%; 3-8mm, 60%;
[0060] The particle size of the composite coated graphite powder is less than 0.04 mm, the particle size of silicon nitride is less than 0.03 mm, the particle size of α-alumina micropowder is less than 0.03 mm, and the particle size of silicon dioxide micropowder is less than 0.03 mm.
[0061] The preparation method of the high-performance hawkbill castable comprises the following steps:
[0062] 1. Preparation of the first aggregate:
[0063] 1.1, dissolve magnesium acetate and basic aluminum acetate in deionized water in proportion, stir and mix evenly, then drop 9wt% of dilute ammonia water at room temperature, and simultaneously drop acetic acid to obtain a magnesium-aluminum mixed solution; the magnesium acetate and basic aluminum acetate are weighed according to a magnesium-aluminum mass ratio of 14:53; the dosage ratio of the magnesium acetate, deionized water, dilute ammonia water, and acetic acid is: 5.2g:18mL:6.8mL:1mL;
[0064] 1.2, alumina, magnesium-aluminum mixed solution and polyvinyl alcohol are mixed, then placed in a ball mill for ball milling, and pressed under 120 MPa to obtain a blank; the amount ratio of alumina, magnesium-aluminum mixed solution and polyvinyl alcohol is 60g:15mL:3g;
[0065] 1.3. Place the blank in a firing kiln, heat it to 1750°C at a rate of 6°C / min, keep it warm for 4 hours, and then crush and classify it to obtain the first aggregate.
[0066] The first aggregate obtained mainly includes corundum phase and aluminum-rich spinel phase; the bulk density is 3.14g / cm 3 The total porosity is 11.5%. The pore size is uniform, mainly concentrated in 8-10 microns. The inner surface of the pore is a micro-nano pore structure formed by an aluminum-rich spinel phase. The thermal conductivity is 6.3W / (m·K) at 700℃. Its microstructure is as follows Figure 1 shown.
[0067] 2. Preparation of composite coated graphite powder:
[0068] 2.1. Mix silicon powder and graphite, grind for 12 minutes, then add boron powder, continue grinding for 12 minutes, then add a uniformly mixed sodium fluoride and potassium fluoride mixed salt, continue mixing for 12 minutes to obtain a mixture; the amount ratio of the silicon powder, boron powder, graphite and mixed salt is 15g:6g:24g:3g; the mass ratio of sodium fluoride and potassium fluoride in the mixed salt is 8:7; the graphite is flaky graphite, the particle size of the graphite is less than 0.025mm, and the particle size of the silicon powder and boron powder is less than 0.01mm.
[0069] 2.2, the mixture is heated to 1400°C in an argon atmosphere and kept at this temperature for 2.5 hours, and then cooled to room temperature; it is repeatedly washed with deionized water, and fully dried at 100°C to obtain composite coated graphite powder.
[0070] The composite coated graphite powder is a graphite structure coated with silicon hexaboride crystals and silicon carbide whiskers; its microstructure is as follows Figure 2 shown.
[0071] 3. Preparation of high-performance eaglebill castables:
[0072] 3.1, premix composite coated graphite powder, silicon nitride, α-alumina powder, silica powder, composite dispersant, barium sulfate, tri(2-hydroxypropionic acid) aluminum salt, activator and calcium aluminate cement in proportion, then add the first aggregate and fused white corundum and mix evenly, then add water and stir evenly, then cast into shape, cure at room temperature for 22 hours, then demold to obtain a cast product; the active agent comprises 41wt% of aluminum oxide, 13wt% of calcium oxide and 18wt% of magnesium oxide, and the active agent d 50 15 microns;
[0073] 3.2, the casting is cured at room temperature for 169h, then heated to 625℃ at a rate of 9℃ / min for the first time, kept warm for 1.5h, and then heated to 800℃ at a rate of 4℃ / min for the second time, kept warm for 4h, to obtain high-performance hawkbill casting material. Example 3
[0074] A high-performance hawkbill castable, comprising the following raw materials by weight: 65 parts of first aggregate, 20 parts of fused white corundum, 15 parts of composite coated graphite powder, 5 parts of silicon nitride, 6 parts of α-alumina micropowder, 2.5 parts of silicon dioxide micropowder, 4 parts of calcium aluminate cement, 0.5 parts of composite dispersant, 0.3 parts of barium sulfate, 7 parts of water, 0.8 parts of tris(2-hydroxypropionic acid)aluminum salt, and 1 part of activator;
[0075] The composite dispersant is a mixture of sodium hexametaphosphate and sodium tripolyphosphate in a mass ratio of 10:5;
[0076] The mass percentage of each particle size in the first aggregate is: 1-3mm, 40%; 3-8mm, 35%; 8-15mm, 15%; 15-25mm, 10%;
[0077] The mass percentages of the various particle sizes in the fused white corundum are: 1-3mm, 30%; 3-8mm, 70%;
[0078] The particle size of the composite coated graphite powder is less than 0.04 mm, the particle size of silicon nitride is less than 0.03 mm, the particle size of α-alumina micropowder is less than 0.03 mm, and the particle size of silicon dioxide micropowder is less than 0.03 mm.
[0079] The preparation method of the high-performance hawkbill castable comprises the following steps:
[0080] 1. Preparation of the first aggregate:
[0081] 1.1, dissolve magnesium acetate and basic aluminum acetate in deionized water in proportion, stir and mix evenly, then drop 10wt% dilute ammonia water at room temperature, and simultaneously drop acetic acid to obtain a magnesium-aluminum mixed solution; the magnesium acetate and basic aluminum acetate are weighed according to a magnesium-aluminum mass ratio of 15:55; the dosage ratio of the magnesium acetate, deionized water, dilute ammonia water, and acetic acid is: 5.5g:20mL:7.2mL:1.2mL;
[0082] 1.2, alumina, magnesium-aluminum mixed solution and polyvinyl alcohol are mixed, then placed in a ball mill for ball milling, and pressed under 120 MPa to obtain a blank; the amount ratio of alumina, magnesium-aluminum mixed solution and polyvinyl alcohol is 70g:20mL:3.6g;
[0083] 1.3. Place the blank in a firing kiln, heat it to 1800°C at a rate of 8°C / min, keep it warm for 3 hours, and then crush and classify it to obtain the first aggregate.
[0084] The first aggregate obtained mainly includes corundum phase and aluminum-rich spinel phase; the bulk density is 3.08g / cm 3 The total porosity is 14.3%. The pore size is uniform, mainly concentrated in the range of 8-10 microns. The inner surface of the pores is a micro-nano pore structure formed by an aluminum-rich spinel phase. The thermal conductivity is 5.6 W / (m·K) at 700°C.
[0085] 2. Preparation of composite coated graphite powder:
[0086] 2.1. Mix silicon powder and graphite, grind for 15 minutes, then add boron powder, continue grinding for 15 minutes, then add a uniformly mixed sodium fluoride and potassium fluoride mixed salt, continue mixing for 20 minutes to obtain a mixture; the amount ratio of the silicon powder, boron powder, graphite and mixed salt is 20g:8g:30g:3.6g; the mass ratio of sodium fluoride and potassium fluoride in the mixed salt is 10:8; the graphite is flaky graphite, the particle size of the graphite is less than 0.025mm, and the particle size of the silicon powder and boron powder is less than 0.01mm.
[0087] 2.2, the mixture is heated to 1500°C in an argon atmosphere for 2 hours, and then cooled to room temperature; it is repeatedly washed with deionized water, and fully dried at 100°C to obtain composite coated graphite powder.
[0088] The composite coated graphite powder is a graphite structure coated with silicon hexaboride crystals and silicon carbide whiskers.
[0089] 3. Preparation of high-performance eaglebill castables:
[0090] 3.1, premix composite coated graphite powder, silicon nitride, α-alumina powder, silica powder, composite dispersant, barium sulfate, tri(2-hydroxypropionic acid) aluminum salt, activator and calcium aluminate cement in proportion, then add the first aggregate and fused white corundum and mix evenly, then add water and stir evenly, then cast into shape, cure at room temperature for 24 hours, then demold to obtain a cast product; the active agent comprises 43wt% of aluminum oxide, 14wt% of calcium oxide and 16wt% of magnesium oxide, and the active agent d 50 20 microns;
[0091] 3.2, the cast product is cured at room temperature for 170h, then heated to 650℃ at a rate of 10℃ / min for the first time, kept warm for 1h, and then heated to 900℃ at a rate of 5℃ / min for the second time, kept warm for 3h, to obtain high-performance hawkbill castable.
[0092] The structure shape of the high-performance hawkbill castable prepared in this embodiment is as follows Figure 4 shown.
[0093] Comparative Example 1
[0094] The same as Example 1, except that the first aggregate is replaced by fused white corundum.
[0095] Comparative Example 2
[0096] The same as Example 2, except that the composite coated graphite powder is replaced by boron powder, graphite and silicon powder; the usage ratio of silicon powder, boron powder and graphite is 15g:6g:24g.
[0097] Comparative Example 3
[0098] The same as Example 2, except that tris(2-hydroxypropionic acid)aluminum salt is used instead of the active agent.
[0099] Performance testing
[0100] According to GB / T2997-2015, GB / T3001-2007, GB / T5072.2-2004, and GB / T3001-2007, the high-performance hawk beak castables prepared in Examples 1-3 and Comparative Examples 1-3 were tested for apparent porosity and bulk density, room temperature flexural strength, room temperature compressive strength, and permanent linear change rate. The high-performance hawk beak castables prepared in Examples 1-3 and Comparative Examples 1-3 were kept at 1600°C for 30 minutes, cooled by high-pressure cold air, and the flexural strength was measured after 5 cycles, and the flexural strength retention rate was calculated; Explosion-proof performance test: The castables after curing in step 3.2 in Examples 1-3 and Comparative Examples 1-3 were placed in an electric furnace, heated to 600°C at a heating rate of 15°C / min, and their bursting was observed. If bursting, the temperature at the time of bursting was recorded. The results are shown in Table 1.
[0101] Table 1. Performance test results
[0102] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Bulk density (g / cm 3 ).]]> 2.91 2.94 2.93 3.47 3.08 3.25 Apparent porosity (%) 18.2 19.7 18.9 8.9 15.5 16.2 Flexural strength (MPa) 22.5 23.1 21.6 17.3 14.8 18.5 Compressive strength (MPa) 112.3 108.6 111.4 88.6 93.9 98.7 Permanent line change rate (%) 0.13 0.15 0.09 0.38 0.32 0.45 Flexural strength retention rate (%) 90.7 92.3 91.5 81.4 78.2 76.4 Burst temperature (℃) No burst No burst No burst 151 122 91
[0103] As can be seen from Table 1, the high-performance hawkbill castables prepared in Examples 1 to 3 of the present application and Comparative Examples 1 to 3 have a small volume density, a large apparent porosity, high flexural strength and compressive strength, a small permanent linear change rate, good expansion resistance, good thermal shock stability, and good burst resistance.
[0104] Corrosion resistance test:
[0105] The high-performance hawk beak castables prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were placed in a furnace and fixed on a rotary shaft. The copper material was poured into the furnace, and the rotary furnace was started. The furnace was heated to 1600°C and heat treated for 4 hours, and then cooled to room temperature with the furnace. The high-performance hawk beak castable was taken out and the erosion depth of the copper molten slag on the same position of the cross section was observed. Figure 3 As shown. Figure 3 It can be seen that the high-performance hawkbill castables prepared in Examples 1 to 3 of the present application have the best corrosion resistance.
[0106] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.
Claims
1. A high-performance hawkbill castable, characterized in that: The raw materials include the following by weight: 45-65 parts of first aggregate, 15-20 parts of fused white corundum, 10-15 parts of composite coated graphite powder, 3-5 parts of silicon nitride, 4-6 parts of α-alumina powder, 2-2.5 parts of silica powder, 2-4 parts of calcium aluminate cement, 0.3-0.5 parts of composite dispersant, 0.1-0.3 parts of barium sulfate, 5-7 parts of water, 0.5-0.8 parts of tris(2-hydroxypropionic acid)aluminum salt, and 0.8-1 parts of active agent; The preparation method of the first aggregate comprises the following steps: 1.1, dissolving magnesium acetate and basic aluminum acetate in deionized water in proportion, stirring and mixing evenly, then dropping (8-10) wt% of dilute ammonia water at room temperature, and simultaneously dropping acetic acid to obtain a magnesium-aluminum mixed solution; 1.2, mixing alumina, the magnesium-aluminum mixed solution, and polyvinyl alcohol, then ball milling, pressing and forming, to obtain a blank; 1.3, keeping the blank at 1700-1800° C. for 3-5 hours, and then crushing and grading to obtain a first aggregate; The preparation method of the composite coated graphite powder is as follows: 2.1, silicon powder and graphite are mixed, ground for 10-15 minutes, then boron powder is added, ground for 10-15 minutes, and then a uniformly mixed sodium fluoride and potassium fluoride mixed salt is added, and mixing is continued for 15-20 minutes to obtain a mixture; 2.2, the mixture is heated to 1300-1500° C. under an argon atmosphere, kept warm for 2-3 hours, and cooled to room temperature; repeatedly washed with deionized water, and after being fully dried, a composite coated graphite powder is obtained.
2. A high-performance hawkbill castable according to claim 1, characterized in that: The magnesium acetate and basic aluminum acetate are weighed according to a magnesium-aluminum mass ratio of 12-15:50-55; the dosage ratio of magnesium acetate, deionized water, dilute ammonia water, and acetic acid is: (4.8-5.5) g: (15-20) mL: (6.5-7.2) mL: (0.8-1.2) mL; the dosage ratio of aluminum oxide, magnesium-aluminum mixed solution, and polyvinyl alcohol is (50-70) g: (10-20) mL: (2.4-3.6) g.
3. A high performance hawkbill castable according to claim 2, characterized in that: The dosage ratio of the silicon powder, boron powder, graphite and mixed salt is (10-20) g: (5-8) g: (18-30) g: (2.4-3.6) g; the mass ratio of sodium fluoride to potassium fluoride in the mixed salt is 6-10: 5-8; the particle size of the graphite is less than 0.025 mm, and the particle sizes of the silicon powder and boron powder are less than 0.01 mm.
4. A high-performance hawkbill castable according to claim 3, characterized in that: The composite dispersant is a mixture of sodium hexametaphosphate and sodium tripolyphosphate in a mass ratio of (8-10): (3-5); the active agent comprises 39-43wt% aluminum oxide, 12-15wt% calcium oxide and 16-20wt% magnesium oxide. 50 10-20 microns.
5. A high performance hawkbill castable according to claim 4, characterized in that: The mass percentages of various particle sizes in the first aggregate are: 1-3mm, 25-40%; 3-8mm, 20-35%; 8-15mm, 12-25%; 15-25mm, 8-15%; the mass percentages of various particle sizes in fused white corundum are: 1-3mm, 30-45%; 8-15mm, 55-70%.
6. A high performance hawkbill castable according to claim 5, characterized in that: The particle size of the composite coated graphite powder is less than 0.04 mm, the particle size of silicon nitride is less than 0.03 mm, the particle size of α-alumina micropowder is less than 0.03 mm, and the particle size of silicon dioxide micropowder is less than 0.03 mm.
7. The method for preparing the high-performance hawkbill castable according to any one of claims 1 to 6, characterized in that: The following steps are involved: 3.
1. Premix the composite coated graphite powder, silicon nitride, α-alumina powder, silica powder, composite dispersant, barium sulfate, aluminum tri(2-hydroxypropionate), activator and calcium aluminate cement in proportion, then add the first aggregate and fused white corundum and mix evenly, then add water and stir evenly, then cast into shape, cure for 20-24h, then demold to obtain a casting; 3.
2. Cure the casting for another 168-170h, then heat it to 600-650℃ for the first time, keep it warm for 1-2h, then heat it to 750-900℃ for the second time, keep it warm for 3-5h, and obtain a high-performance hawkbill casting material.
8. The method for preparing the high-performance hawkbill castable according to claim 7, characterized in that: The first heating rate is 8-10°C / min, and the second heating rate is 3-5°C / min.
Citation Information
Patent Citations
Corundum-aluminum spinel castable, preparation method thereof and preparation method of corundum-aluminum spinel
CN108046782A
Preparation method of aluminum-magnesium-carbon castable containing modified micro-nano graphite flakes
CN118344130A